Giant bulla or pneumothorax: How to distinguish. (2019) - Aramini, Beatrice; Ruggiero, Ciro; Stefani, Alessandro; Morandi, Uliano
Highlights: The differential diagnosis between pneumothorax and giant bulla is not straightforward. We emphasized how to differentiate between giant bulla and pneumothorax. The complexity to differentiate induces to make mistakes in diagnosis and in treatment decision. Chest CT is mandatory in case of the impossibility to understand the radiological findings. Abstract: Background: The differential diagnosis between pneumothorax and giant bullae is thought to be straightforward but sometimes poses a challenge. Case presentation: We present a case of a 54-year-old Caucasian man with a giant emphysematous bulla who underwent surgical resection. He had no smoking history and had previous pneumonia episodes. The surgery was free of complications, without air leaks, and he showed good ventilation of the lung. Discussion: The main complications of bullae are pneumothorax, infection and hemorrhage. Pneumothorax is a serious complication in patients with compromised lung function. Therefore, it is very important to carefully distinguish bullae from pneumothorax to avoid iatrogenic pneumothorax in patients with bullous disease. Conclusion: We emphasize how to differentiate between giant bullae and pneumothorax utilizing history, physical examination, and radiological studies, including computed tomography (CT) scan.